Toxicity and possibly Reduced Graphene Oxide cellular interaction with Raphidoceles subcapitata: Ultrastructural analysis (Research, Society and Development, 2021)
Reduced graphene oxide (rGO) is a nanomaterial formed by carbon, presented as a graphene oxide derivative, and due to its properties, it is used in areas such as in microelectronics, mechanics, and biomedicine. Despite a large number of tests conducted with this nanomaterial, there is not yet a consensus about its toxicity, when in the environment. The aquatic environment is usually the final destination of those compounds and, for this reason, the green algae is often used as a bioindicator. This study aimed to determine the ecotoxicity and possible interactions of the rGO nanoparticle with the   green algae cell of Raphidocelis subcapitata. The structural changes in the algae, exposed to different concentrations the rGO, were analyzed through transmission electron microscopy (TEM) and Raman spectroscopy, the toxicity was assessed by measure the inhibition of algal biomass. The results indicate that there was no toxic effect on the studied organism, except in the higher concentration (100 mg.L -1). TEM analysis demonstrated an interaction of the nanoparticles with the algal cell, by observation of the internalization of the nanoparticles, as well as by rGO deposition on the cell membrane.  Despite the absence of toxicity at low concentrations, the organisms showed sensitivity to the presence of the rGO. Those results contribute to the literature in the clarification of the behavior of carbon-based nanoparticles in the aquatic environment and may allow better care with the production and release of those nanoparticles in the environment.